A Fair Possibility of Tracking Scientific Retractions through Crossref for Sustainability of Science - Kar, Sanjoy (Journal of Data Science, Informetrics, and Citation Studies)
Crossref's acquisition of the Retraction Watch database, announced on September 12, 2023, heralds a transformative era in research integrity. This commentary highlights the pivotal role played by this acquisition in preserving the trustworthiness of scientific research. By creating the most extensive open-source retraction database, it streamlines the identification of retractions, enhancing transparency and accessibility. Open access ensures global availability, benefiting researchers, publishers, and readers. Financial support secures sustainability, enabling the expansion of investigative journalism on retractions. This acquisition demonstrates the collective commitment to upholding rigorous scientific standards and advancing the future of research.
Keywords: Retraction Watch; Crossref; Center for Scientific Integrity; Academic publishing; Scientific Misconducts; Retracted Publications; Sustainability of Science; Research Nexus; Research Integrity; Open-source database.